Knowledge, motivation, attitude, job design and health cadre performance: a cross sectional study - Rinayati Rinayati; Harsono Harsono; Ambar Dwi Erawati (International Journal of Public Health Science (IJPHS), 2023)
In 2020, the maternal mortality rate in Semarang increased to 98.6/100,000 and was ranked in the top 10 highest in Central Java. Until November 2021, there were 111 cases of Infant Mortality Rate (IMR), 195 cases of dengue fever, and 210 cases of malnutrition. The performance of health cadres and the role of the community must be improved. The results of observations in the field, the working cadres are still limited, and the performance of health cadres is considered not optimal. This cross-sectional study aimed to knowing the influential factors on performance of health cadres. The population of this study was all health cadres. The number of research samples was 68 respondents determined through the quota sampling. The source of data used in this study was primary data obtained through direct interviews using structured questionnaires. Data analysis used frequency distribution, bivariate, and multivariate analyses. Most of the health cadres have performed well (73.5%). The attitude of health cadres is the most influential factor on the performance of health cadres in improving health status in their area (p-value=0.001).